A simple computational procedure for optimization problems with functional inequality constraints - Teo, K.; Goh, C. (IEEE transactions on automatic control, 1987)
In this note, a simple computational procedure is given for solving a class of optimization problems, where an objective function is to be minimized subject to conventional inequality constraints as well as to inequality constraints of the functional type.